The Effect of Comparison of Wheat and Avocado Seed Flour (Persea americana) on Biscuit Characteristics - Swasni Prambandita, Kadek Dyah; Suter, I Ketut; Putu Gunadnya, Ida Bagus (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 9 No 1 (2022): Scientific Journal of Food Technology (March), 2022)
Avocado seeds are one part of the plant that has not been widely used by the community. The fiber and natural antioxidants content of avocado seeds can be used as functional food. The utilization of avocado seeds flour in biscuit products is expected to make it easier for people to enjoy snacks and get its health benefits. This study aims to determine the effect of the ratio of wheat flour and avocado seed flour to the characteristics of biscuits, to determine the ratio of wheat and avocado seed flour to obtain the best characteristics of the  biscuits, and examine the effect of the best mixed flour and avocado seed flour on blood sugar levels in mice. This research consisted of 2 stages. The first stage used a completely randomized design with a treatment ratio of wheat and avocado seed flour, namely F1 (100: 0), F2 (90:10), F3 (80:20), F4 (70:30), F5 (60:40) , F6 (50:50). Determination of the best biscuits was done based on the observed parameters, namely: chemical test (protein test, moisture test, fat test, ash content test, crude fiber test, antioxidant capacity, IC50 value). After obtaining the best product, the research was continued with the second  stage, namely feed treatment using male Wistar mice weighing 20-30 g for 8 days by comparing the initial and final blood sugar levels. Mice were grouped into 3 groups based on the feed given, namely the DM group with standard feeding, the second group DM mice with standard feed mixed with the best biscuits, the third group with feeding only the best biscuits. The results showed that the formulations of wheat and avocado seed flour had an effect on the characteristics of the biscuits, namely color L, a, b, protein content, moisture content, fat content, ash content, crude fiber content, antioxidant capacity and IC50. The ratio of wheat flour and avocado seed flour that produced the best biscuit characteristics was the 50:50 formulation with the following characteristics: 5.60% protein content, 3.04% ash content, 4.94% moisture content, 32.25% fat content, 28, 03% carbohydrate content, 25.12% crude fiber, 7664 ppm IC50, 517.8307 mg GAE / kg antioxidant capacity, 25.73 L value, 22.81 a value, and 21.62 b value. Mixed flour and The best avocado seed flour reduce blood sugar levels in mice by 33.49%